Floating Marine Litter in Eastern Mediterranean From Macro to Microplastics: The Lebanese Coastal Area as a Case Study - Jemaa, Sharif; Mahfouz, Celine; Kazour, Maria; Lteif, Myriam; Hassoun, Abed El Rahman; Ghsoub, Myriam; Amara, Rachid; Khalaf, Gaby; Fakhri, Milad (Frontiers in Environmental Science, 2021)
Despite emerging and increasing concerns related to marine micro and macroplastics, no systematic surveys have been undertaken yet in the Lebanese marine area. To understand the spatio-temporal variation of plastic litter (macro and microplastics) in the Lebanese marine environment and determine the sources of pollution, this study investigated the characteristics of plastic pollution in sea surface waters during wet and dry seasons in 22 sites of Beirut and Tyre regions. A total of 23023 items were identified and assessed according to the shape, color, and concentration; moreover, the risk of microplastics (MPs) contamination was explored based on a risk assessment model. The obtained results demonstrated that the average macroplastics concentration was 0.45±0.6 items/m3. The average microplastics concentration was found to be 20.1±21.8 and 3.78±5.2 items/m3 in spring and fall respectively. During fall, MP fragments were dominant in Beirut (97%) and Tyre (91%), and no pellets were observed. During spring, filaments were most encountered in Beirut (76.5%). The most dominant marine litter color was blue followed by black and white. According to the Pollution Load Index (PLI) values, the marine water along the Lebanese coast is moderately contaminated with MPs (PLI: 5.79 ± 3.93) except for several sites from Beirut that showed high values of PLI, highlighting the local influence of cities and rivers on MP concentration. This study is an important baseline for understanding the characteristics of the seasonal variation of MPs along the Lebanese marine environment; it will help stakeholders and countries to take proactive and reactive actions to face plastic litter pollution in the Lebanese coastal area.